After surgery: the effects of life-saving caesarean sections in Burkina Faso. Issue 1 (December 2015) - Filippi, Véronique; Ganaba, Rasmané; Calvert, Clara; Murray, Susan; Storeng, Katerini
Abstract Background In African countries, caesarean sections are usually performed to save mothers and babies' lives, sometimes in extremis and at considerable costs. Little is known about the health and lives of women once discharged after such surgery. We investigated the long-term effects of life-saving caesarean section on health, economic and social outcomes in Burkina Faso. Methods We conducted a 4 year prospective cohort study of women and their babies using mixed methods. The quantitative sample was selected in seven hospitals and included 950 women: 100 women with a caesarean section associated with near-miss complication (life-saving caesareans); 173 women with a vaginal birth associated with near-miss complication; and 677 women with uncomplicated vaginal childbirth. Structured interviews were conducted at 3 months, 6 months, 12 months and 3 and 4 years postpartum. These were supplemented by medical record data on delivery and physical examinations at 6 and 12 months postpartum. The lives and experiences of 21 women were documented ethnographically. Data were analysed with multivariable logistic regressions, using survival analysis and thematic analysis. Results The physical effects of life-saving caesareans appeared to be similar to women who had an uncomplicated childbirth, although 55 % of women with life-saving caesareans had another caesarean in their next pregnancy. The negative effects were generally economic, social and reproductive when compared to vaginal births, including increased debts (AOR = 3.91 (1.46–10.48) and sexual violence (AOR = 4.71 (1.04–21.3)) and lower fertility (AOR = 0.44 (0.24–0.80)) 4 years after life-saving caesareans. In the short and medium term, women with life-saving caesareans appeared to suffer increased psychological distress compared to uncomplicated births. They were more likely to use contraceptives (AOR = 5.95 (1.53–23.06); 3 months). Mortality of the index child was increased in both near-miss groups, independent of delivery mode. Ethnographic data suggest that these consequences are significant for Burkinabe women, whose well-being and social standing are mostly determined by their fertility, marriage strength and family links. Conclusions Life-saving caesareans have broad consequences beyond clinical sequelae. The recent policy to subsidise emergency obstetric care costs implemented in Burkina Faso should help avoid the majority of catastrophic costs, shown to be problematic for women undergoing emergency caesarean section.